EVOLUTION OF DISPUTE RESOLUTION THROUGH ARBITRATION IN INDONESIA DURING COVID-19 - Mohammad Saleh (Arena Hukum, 2023)
Settlement of disputes in civil cases is not only resolved by the Court, but also through arbitration and alternative dispute resolution if the disputing parties agreed. The selection of this arbitration must be stated in the clause of the agreement which expressly chooses the arbitration. Civil cases that become the authority of this arbitration are only within the scope of the trade sector. The procedure for settlement through arbitration is different from the court, among others, the trial is closed and flexible, the decision is final and binding, the arbitrator is chosen by the parties and the decision is carried out by the court.